2016
DOI: 10.1093/schbul/sbw135
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Cognition and Psychosis in Young Adults With 22q11.2 Deletion Syndrome

Abstract: Our data are the first to go beyond IQ assessments in assessing longitudinal neuropsychological outcomes and risk for psychosis in 22q11DS. Individuals with 22q11DS who developed psychotic symptoms improved less appreciably and continued to demonstrate difficulties with cognitive flexibility relative to individuals with 22q11DS who did not have psychotic symptoms. Individuals with 22q11DS who developed psychosis had weaker reading skills in childhood and, after an initial improvement into adolescence, these in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 40 publications
5
53
0
Order By: Relevance
“…Given that cognitive impairment is characteristic of 22q11.2DS, it is important to note that, while the cognitive decline that seems to precede and predict the development of psychosis in idiopathic schizophrenia (110,111) might be somewhat conspicuous, such a decline may not be as noticeable in 22q11.2DS and might require more thorough monitoring. Indeed, in 22q11.2DS, cognitive deficits may be traits that preexist and increase risk for psychosis, but, keeping in mind this shifted baseline, should still allow one to discriminate those most susceptible to psychotic symptoms (112). Additionally, increased variability was observed in the 22q11.2DS group, both in the N1 and the MMN time windows, in line with the remarkable variability in expression described in the syndrome (6,(113)(114)(115).…”
Section: Discussionmentioning
confidence: 77%
“…Given that cognitive impairment is characteristic of 22q11.2DS, it is important to note that, while the cognitive decline that seems to precede and predict the development of psychosis in idiopathic schizophrenia (110,111) might be somewhat conspicuous, such a decline may not be as noticeable in 22q11.2DS and might require more thorough monitoring. Indeed, in 22q11.2DS, cognitive deficits may be traits that preexist and increase risk for psychosis, but, keeping in mind this shifted baseline, should still allow one to discriminate those most susceptible to psychotic symptoms (112). Additionally, increased variability was observed in the 22q11.2DS group, both in the N1 and the MMN time windows, in line with the remarkable variability in expression described in the syndrome (6,(113)(114)(115).…”
Section: Discussionmentioning
confidence: 77%
“…51,55 Comparable patterns of impairments evident in clinical high-risk populations, 56,57 and family members of patients, 58,59 implicate these as potential endophenotypes. Similar impairments in executive function, social cognition, non-verbal memory, working memory and visual-spatial function in 22q11DS, 24,4547,6062 suggest possible sharing of underlying neural networks.…”
Section: Schizophrenia Spectrum and Brain Behavior Parameters In 22q11dsmentioning
confidence: 89%
“…4244 With a known high-risk for schizophrenia, 22q11DS provides the opportunity to systematically investigate early abnormalities in development as well as the emergence of psychotic illness in cross-sectional and prospective studies of individuals who share the same genetic abnormality. 4547 Investigations applying standard procedures to assess subthreshold psychotic symptoms in 22q11DS have reported their presence across samples. 4850 Integration of phenotypic parameters with genomics may generate mechanistic insights that lead to improved clinical diagnosis and offer new therapies.…”
Section: Schizophrenia Spectrum and Brain Behavior Parameters In 22q11dsmentioning
confidence: 99%
“…Furthermore, it has been reported that longitudinal cognitive profiles were similar between children with 22q11.2DS and IQ-matched and age-matched children with idiopathic intellectual disabilities (IID; Van Den Heuvel 25 ). Examining impairments in specific cognitive domains such as attention may provide insights into neurobiological processes 11 and that these functions may be more sensitive both to cognitive change and to remediation strategies than a global measure of intelligence like IQ 26 .…”
Section: Introductionmentioning
confidence: 99%